IONIC SUBSTITUTIONS IN THE OCTAHEDRAL SITES AND STRUCTURAL CHANGES IN CA-EPIDOTE GROUP MINERALS - Nagashima M.; Akasaka M. (My University, 2004)
Epidote group is important rock-forming minerals which form in a variety of geological conditions. Crystal structure of epidote contains 9-coordinated A1 and 10-coordinated A2 sites, and three kinds of octahedral sites, M1, M2, and M3. Various cations can occupy the A and M sites, and consequently epidote group minerals have a wide range chemical compositions. Natural Ca-epidote group minerals contain several transition elements, including Fe, Mn, Cr and V, and their occurrence, chemical composition and crystal chemistry have thus been studied in some detail. Crystallographic studies of synthetic epidote group minerals on the Ca2Al3Si3O12(OH)(Cz)-Ca2Fe33+Si3O12(OH) and Cz-Ca2Mn33+Si3O12(OH) joins have shed much light on the contribution of each ionic substitution to their crystal structures. In this paper, we review studies of the ionic substitutions in the octahedral M1, M2, and M3 sites in Ca-epidote group minerals, and the influence of these substitutions on structural changes.